2023
DOI: 10.21037/atm-22-4663
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous catheter drainage versus needle aspiration for liver abscess management: an updated systematic review, meta-analysis, and meta-regression of randomized controlled trials

Abstract: Background Liver abscess is a life-threatening condition. Percutaneous catheter drainage (PCD) and percutaneous needle aspiration (PNA) are both minimally invasive techniques used to manage liver abscess. We aim to compare both techniques’ efficacy and safety. Methods We performed a systematic review and meta-analysis involving randomized controlled trials (RCTs) from PubMed, Embase, Scopus, WOS, Cochrane, and Google scholar until July 22 nd ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 56 publications
(124 reference statements)
3
13
0
2
Order By: Relevance
“…In terms of PCD treatment efficacy, complications and clinical improvement, two additional recently published meta-analyses yielded similar results to our study 35 36. Based on abscess size and pus volume, Mahmoud et al performed meta-regression analysis 36. Our meta-regression analysis supported their conclusion regarding the association between abscess size and treatment efficacy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In terms of PCD treatment efficacy, complications and clinical improvement, two additional recently published meta-analyses yielded similar results to our study 35 36. Based on abscess size and pus volume, Mahmoud et al performed meta-regression analysis 36. Our meta-regression analysis supported their conclusion regarding the association between abscess size and treatment efficacy.…”
Section: Discussionsupporting
confidence: 88%
“…In terms of PCD treatment efficacy, complications and clinical improvement, two additional recently published meta-analyses yielded similar results to our study 35 36. Based on abscess size and pus volume, Mahmoud et al performed meta-regression analysis 36.…”
Section: Discussionsupporting
confidence: 86%
“…In addition to antibiotic treatment, percutaneous intervention is also an important intervention for patients with PLA, because rapid removal of pus can significantly shorten the hospital stay, improve patient prognosis, and reduce hospitalization costs [ 1 ]. Over the past two decades, PNA and PCD have played increasingly important roles in treating liver abscesses, although there is still considerable debate as to which is superior [ 27 , 28 ]. Our KPPLA and non-KPPLA groups both had higher prevalences of infections in the right liver, possibly because of the larger size of the right hepatic lobe and because this lobe receives a greater portal blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…Our overall treatment success rate (from PNA or PCD) was 89.61 %, and was unrelated to the causative pathogen. Some recent studies suggested were some differences in the efficacy of PCD and PNA depending on abscess size and pathogen species [ 1 , 27 , 28 ]. We also compared the effects of different modalities of pus removal in the KPPLA and non-KPPLA groups; there was no difference for the non-KPPLA group, but PNA was superior to PCD in the KPPLA group in terms of hospital stay and hospital costs, although both modalities provided good safety and efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Under imaging guidance, usually ultrasound or CT, abscesses can be drained percutaneously. This minimally invasive approach has become a first-line treatment for many abscesses, especially when they are easily accessible and not complicated by fistulas or multi-loculated collections [ 17 ]. Some abscesses, especially those that are multi-loculated, associated with a fistula, or not amenable to percutaneous drainage (PD), require surgical intervention.…”
Section: Introductionmentioning
confidence: 99%